Tube thoracostomy during the COVID-19 pandemic: guidance and recommendations from the AAST Acute Care Surgery and Critical Care Committees. Issue 1 (30th April 2020) - Pieracci, Fredric M; Burlew, Clay Cothren; Spain, David; Livingston, David H; Bulger, Eileen M; Davis, Kimberly A; Michetti, Christopher
Abstract : This document provides guidance for trauma and acute care surgeons surrounding the placement, management and removal of chest tubes during the COVID-19 pandemic.